2008
DOI: 10.3354/dao01952
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal alterations in male whitefish Coregonus fatioi: no evidence for genetic damage reducing viability in early life stages

Abstract: In recent years, numerous cases of morphological gonadal alterations in fish have been recorded throughout the world and across a wide range of species. In the whitefish Coregonus fatioi from the pre-alpine Lake Thun (Switzerland), the frequency of gonadal alterations is particularly high and the variety of alteration types large. Little is known about the proximal causes and the direct consequences of these morphological features on population persistence. In particular, the potential for the observed alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…This result is consistent with other salmonid studies employing various group-rearing conditions (e.g. Beacham 1988;Nagler et al 2000;Urbach et al 2008;Janhunen et al 2010). Janhunen et al (2010) and others suggested that detecting paternal effects at embryonic stages depends on the kind and amount of environmental variance allowed for in the experiment, a prediction verified in recent studies on brown trout (Jacob et al 2010) and whitefish Coregonus palaea (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…This result is consistent with other salmonid studies employing various group-rearing conditions (e.g. Beacham 1988;Nagler et al 2000;Urbach et al 2008;Janhunen et al 2010). Janhunen et al (2010) and others suggested that detecting paternal effects at embryonic stages depends on the kind and amount of environmental variance allowed for in the experiment, a prediction verified in recent studies on brown trout (Jacob et al 2010) and whitefish Coregonus palaea (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the increased prevalence of gonad malformations in Lake Thun coregonids is unlikely to represent a genetic predisposition. This interpretation is supported by the findings of Urbach et al [41] and Bittner et al [35]). Finally, the fact that the prevalence of gonad malformations in Lake Biel whitefish reared in Lake Thun water and fed with Lake Thun zooplankton did not differ significantly from the prevalence of gonad malformations in Lake Thun whitefish reared under identical conditions argues against a contribution of "gene × environment" interaction.…”
Section: Discussionsupporting
confidence: 63%
“…To assess further on a more precise level, research on histology was conducted because it is crucial in identifying the detrimental impact of pollutants on living tissues. 30,31 A primary lamella (Pl) with a robust central venous (Cv), operational erythrocytes (Ey), mucus cells (Mc), chloride cells (Cc), and basal undifferentiated cells (Bu) was seen in the histopathological examination of control fish gill tissue (Figure 1G1). Coherent capillary-lumen lacuna (Cl), pillar cells (Pc), and intact epithelial layers (El) with a normal interfilament spacing (Ifs) were also prominently evident in the secondary lamellae (Sl) of the control group gill.…”
Section: Resultsmentioning
confidence: 99%